Merchants, Markets and Manufacture - Smail, J. author. aut Link
X, 198 p.
Keywords: This book explores the causes and nature of the industrial revolution through a comparative study of the main wool textile manufacturing regions of England. Addressing many of the current debates in economic history and eighteenth-century studies through a detailed, archivally-based analysis, it examines how the interplay between merchants, markets and producers shaped the pace and character of economic growth during the eighteenth century, paying particular attention to the implications of rapid product innovation and the export trade.